(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2018)
This paper tackles a little place in the history of the Chilean Catholic Church. It talks about the worker priests’ arrival and specifically about the Calama experience, an unprecedented process in the history of the church, whose main aim was the transformation of the old and bourgeois Catholic structures into a Nazarene dedicated church of and for the poor. Influenced by the structural changes defined by the Catholic Church since the Second Vatican Council, the theology of liberation and Medellin 1968, the so-called ‘Calama experience’ sees an end in 1973. Nonetheless, its inspirations and pursuits remain latent in the path of the movement generated by the ‘Equipo de Misión Obrera (EMO)’.